Factors Influencing Success Rate of Referral for Asphyxiated Newborns Before and After Helping Babies Breathe (HBB) Training - Yurico, Ariq Azky Yurico; -, Adhie Nur Radityo; Putri Sekar Wiyati; Dimas Tri Anantyo (Basic and Applied Nursing Research Journal, 2023)
Introduction: Referral for asphyxia newborns is the process of transferring newborns with difficult breathing conditions from one health facility to another. Emergency management of asphyxia newborns must be handled properly; one of the examples is taught in a Helping Babies Breath (HBB) training. Other factors that influence the determinants of referral are positive-pressure ventilation action, the state of hypothermia, and the duration of referral. Methods: The research design used in this study was cross-sectional. The samples were collected by purposive sampling from January 2019 to December 2020 from the medical records of Puskesmas Kabupaten Grobogan. Results: There was no significant association between the success rate of referral for asphyxia newborns and the Helping Babies Breathe (HBB) training (p=0.213). Before the HBB was implemented, there was no significant association between the incident and positive-pressure ventilation action (p = 0.092). Still, there was a significant association between the incidence of hypothermia (p=<0.001) and referral duration (p=0.011). After the HBB was implemented, there was no significant association between the incident with positive-pressure ventilation action (p=0.758) and the duration of the referral (p=0.2). Still, there was a significant association with the incidence of hypothermia (p=0.002). Conclusion: There is a significant association between the success rate of referral of asphyxia newborns and hypothermia before and after the HBB Program was implemented and the duration of referrals before the HBB Program was implemented.